Perceived quality of internships and employability perceptions: The mediating role of career-entry worries - Ebner, Katharina; Soucek, Roman; Selenko, Eva (Education and Training, 2021)
This study illuminates the assumption that internships facilitate labor market entry and answers the question of why internships have a positive effect on students’ self-perceived employability. It is assumed that internships enable more positive employability perceptions by reducing career-entry worries – the worries of not finding a suitable job or not being able to obtain a satisfactory career. A two-wave study among graduate students currently in an internship investigated these relationships. Data on career-entry worries, perceived employability and an evaluation of the internship were collected from 80 students (mean age: 24.6 years, 68% female) from various fields of study aiming at both Bachelor’s and Master’s degrees. The results showed that positively-evaluated internships contributed to graduates’ self-perceived employability by means of reduced career-entry worries over an eight week period. By considering graduates’ career-entry worries – the perceived uncertainty about finding an ‘appropriate’ career in the future – the authors introduce a new concept to the career literature and show that these worries are significant in terms of self-assessed employability.<br